2015
DOI: 10.1002/adfm.201403095
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoclusters‐Based Nanoprobes for Simultaneous Fluorescence Imaging and Targeted Photodynamic Therapy with Superior Penetration and Retention Behavior in Tumors

Abstract: Gold nanoclusters (GNCs) attract increasing attention due to their potential applications in sensing, catalysis, optoelectronics, and biomedicine. Herein, the formation of highly fluorescent glutathione (GSH)‐capped GNCs is achieved through the delicate control of the reduction kinetics and thermodynamic selection of the Au(I)–SG complexes. Furthermore, the GNCs‐based nanoprobes are developed by the covalent coupling folic acid (FA) and PEG (polyethylene glycol) on the surface of GNCs directly, followed by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(155 citation statements)
references
References 41 publications
2
153
0
Order By: Relevance
“…Those metal NCs, mainly gold, are made of ten to hundred atoms and usually presented as species filling the gap between molecules and nanoparticles. [1][2][3][4] Gold nanoclusters (Au NCs) present several features making them appealing for cancer therapy thanks to (i) their high renal clearance 5,6 reducing toxicity risk, (ii) the relatively high tumor retention by passive uptake, 7,8 (iii) the ability to trigger cell death under light illumination 9 or radiosensitization, [10][11][12] and (iv) the detection by multimodal imaging techniques. [13][14][15] In optical imaging, one of the great advantages of Au NCs compared to plasmonic Au nanoparticles (Au NPs) is related to the ability to visualize them by fluorescence in the red-near-infrared (NIR) region (650-800 nm), a spectral window suitable for in vivo studies due to the reduced tissue scattering and low blood absorption.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…Those metal NCs, mainly gold, are made of ten to hundred atoms and usually presented as species filling the gap between molecules and nanoparticles. [1][2][3][4] Gold nanoclusters (Au NCs) present several features making them appealing for cancer therapy thanks to (i) their high renal clearance 5,6 reducing toxicity risk, (ii) the relatively high tumor retention by passive uptake, 7,8 (iii) the ability to trigger cell death under light illumination 9 or radiosensitization, [10][11][12] and (iv) the detection by multimodal imaging techniques. [13][14][15] In optical imaging, one of the great advantages of Au NCs compared to plasmonic Au nanoparticles (Au NPs) is related to the ability to visualize them by fluorescence in the red-near-infrared (NIR) region (650-800 nm), a spectral window suitable for in vivo studies due to the reduced tissue scattering and low blood absorption.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…By comparison with free Ce6 (641 nm), the UV-Vis spectroscopy also indicated that there was a significant bathochromic shift in the region of the Ce6 Q(I) band of nanoprobe-4 nm (665 nm), nanoprobe-8 nm (673 nm) and nanoprobe-13 nm (660 nm), which is a typical characteristic of Ce6 in different chemical environments. 8 The results indicated that free Ce6 was successfully encapsulated by the NPO. Interestingly, the characteristic peak intensity of the three types of nanoprobes (700 nm) in the region of the Ce6 Q (II) band was markedly higher than that of free Ce6.…”
Section: Synthesis and Characterization Of Fe 3 O 4 @P-npo/peg-glc@cementioning
confidence: 95%
“…8 To confirm the phototoxicity of the three types of Fe 3 O 4 @P-NPO/PEG-Glc@Ce6 nanoprobes, the standard DCFH-DA staining protocol was carried out to evaluate their ability to generate intracellular singlet oxygen. As shown in Figure 6a, without the laser, the synthesized nanoprobes produced singlet oxygen with a similar ability, slightly more than free Ce6.…”
Section: Photodynamic Therapy Of Ultra-small Fe 3 O 4 @Polymer-npo/pementioning
confidence: 99%
See 1 more Smart Citation
“…Au-NCs have attracted more attention in the past decade because of their ultra small size, excellent luminescence properties and stable structures or good storage stability [11][12][13][14]. In the recent years, gold nanoparticles have emerged for delivery of various payloads into their targets [15][16][17][18][19][20]. The payloads include small molecule drugs and big molecular proteins such as antibody and peptide.…”
Section: Introductionmentioning
confidence: 99%